2020
DOI: 10.47992/ijmts.2581.6012.0099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Performance Review and Faculty Development to Organizational Climate

Abstract: Faculty performance review, faculty development, and organizational climate are an essential element of the educational institution. More importantly, the mentioned variables have certain connections and interplay with each other. This study describes the performance review, faculty development, and organizational climate of a tertiary education institution. This study used a descriptive-correlation design. 56 faculties took part in the survey using a convenience sampling technique. The researcher adopted and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
1
6
0
1
Order By: Relevance
“…These suggest that the teachers need further training with the use of hyperlinks to be able to come up with their instructional material that fits their learners. In a separate context, a study found that in terms of faculty development, the office/ department encourages continual learning and development [22,23]. 6 presents a proficient extent of knowledge of teachers in Microsoft Publisher with an average weighted mean of 2.75.…”
Section: Resultsmentioning
confidence: 99%
“…These suggest that the teachers need further training with the use of hyperlinks to be able to come up with their instructional material that fits their learners. In a separate context, a study found that in terms of faculty development, the office/ department encourages continual learning and development [22,23]. 6 presents a proficient extent of knowledge of teachers in Microsoft Publisher with an average weighted mean of 2.75.…”
Section: Resultsmentioning
confidence: 99%
“…High-quality and professional employees have closely relate to organizational climate in the workplace (Ayalon et al, 2017). Jimenez et al (2020) and Bianome et al (2016) state that there is a positive and significant effect between professionalism Work has a positive and significant effect on Organizational Climate. Organizational climate is beneficial for individual needs in an organization with employees whose interests are considered by the organization, these employees will feel satisfaction at work (Adeniji et al, 2018;Ling Kee et al, 2018).…”
Section: Organizational Climatementioning
confidence: 99%
“…Generally, teachers expect principals to be knowledgeable about all aspects of the school system, so they look up to them to provide the necessary impetus for the adequate performance of their jobs. Studies show that good leaders provide for their constituents by planning for appropriate professional development schemes [6] [7], developing their professional skills and work ethics [8], and mental and physical well-being like sufficient sleep or religious task [9]. In addition, such professional conduct and attribute by the teachers will evade any forms of inappropriate behavior like bullying from students [10] [11].…”
Section: Literature Reviewmentioning
confidence: 99%